Analysis of the Influence of the Tourism Sector on Central Lombok Regional Original Income (PAD) in 2014-2023 - Stiawati, Tumi; Manan, Abdul; Astuti, Endang (West Science Accounting and Finance, 2025)
This study aims to analyze the Influence of the Tourism Sector on Central Lombok's Regional Original Revenue (PAD) in 2014-2023. The tourism sector has an important role in increasing regional revenue through hotel, restaurant, and tourist attraction levies. The independent variables in this study include the number of tourists, the number of tourist attractions, the number of restaurants and restaurants, and the number of hotels, while the dependent variable is Regional Original Revenue (PAD). The research method used is multiple linear regression analysis with secondary data obtained from the Central Statistics Agency (BPS), BAPPEDA, and the Central Lombok Regency Tourism Office. The results of the study show that the number of tourists, the number of tourist attractions, the number of hotels partially and simultaneously have a positive and significant effect on Regional Original Revenue (PAD), while the number of restaurants and eateries partially and simultaneously have a negative and significant effect on Regional Original Revenue (PAD). This research gives implications that local governments need to continue to develop the tourism sector by increasing the number of tourist attractions, the number of restaurants and restaurants, and the number of hotels. Improving tourism infrastructure, as well as optimizing regional taxes and levies to increase Regional Original Revenue (PAD), in addition to this, sustainable tourism management is also needed to maintain tourist attraction and encourage regional economic growth.